Characteristics and Performance of Xanthan Gum–Kappaphycus alvarezii Mixture for Increasing Oil Recovery in Reservoirs with High Salinity - Septianingrum, Wydhea Ayu; Abdillah, Ridho; Iqlimah, Madhu A’la Zulaiqoh; Fathaddin, Muhammad Taufiq; Husla, Ridha; Insani, Andon; Kartini, Rachmi; Andrianaivo, Lala (Journal of Earth Energy Science, Engineering, and Technology, 2026)
Polymer flooding is an effective Enhanced Oil Recovery (EOR) method; however, challenges arise in reservoir conditions with high salinity and temperature, which can degrade conventional polymers. This study aims to analyze the rheological characteristics and sweeping performance of a polymer mixture consisting of Xanthan Gum (XG) and a natural additive from red seaweed, Kappaphycus alvarezii (KA). The research methodology includes viscosity testing against variations in temperature and salinity (30,000–50,000 ppm), contact angle measurements for wettability evaluation, adsorption tests in porous media, and coreflooding experiments. The novelty of this research lies in the utilization of Kappaphycus alvarezii as a natural performance-enhancing agent for XG capable of significantly improving fluid-rock interactions. The results indicate that the addition of KA provides a synergistic effect in increasing solution viscosity and stability. Contact angle measurements prove that KA is much more effective in altering rock wettability to water-wet with a value of 29°, compared to XG at 87°, thus being more optimal in releasing oil from rock pores. Adsorption tests showed an increase in polymer retention as salinity rose, yet remained within operational tolerance. In the coreflooding stage, a 12,000ppm solution at 30,000 ppm salinity yielded the highest incremental recovery factor of 13.33%. Overall, the study concludes that the XG-KA mixture has high potential for application in high-salinity reservoirs due to its superiority in mobility control and wettability modification compared to the use of single polymers.